Effects of Sliding Speed on Wear Behavior of High-Velocity Oxygen Fuel-Sprayed FeCrMoNiCuBSiC Metallic Glass Coatings - Lei Qiao; Botao Zhou; Ruifeng Li; Taotao Li; Yue Zhao; Xiaoqiang Zhang; Chul-Hee Lee (Lubricants)
A FeCrMoNiCuBSiC metallic glass coating was designed and then deposited by the high-velocity oxygen fuel (HVOF) spraying technique. X-ray diffraction, a scanning electron microscope, and a microhardness tester were applied to characterize the phase, microstructure, and mechanical properties of the coating. The amorphous phase was the main phase in the coating, and crystal phases were almost undetectable in the XRD results. The coating had a dense structure (the porosity was 1.47 ± 0.32%) and high Vickers microhardness (848 ± 22 HV0.3). The wear behavior of the coatings sliding against WC-Co was studied with a pin-on-disc wear test system and was compared with that of 316L stainless steel. The coating improved the wear resistance of the steel by around 7–9 times at different sliding speeds. As the sliding speed was increased, the wear loss rate of the steel obviously increased, yet the loss rate of the coating decreased first and then increased. This happened because the contact flash temperature induced by friction increases with the sliding speed, which results in oxidative behavior and crystallization events in the coating. The dominating wear mechanism of the coating is fatigue wear combined with oxidative wear.